Epidemiology of Acute Lower Respiratory Tract Infections in Children - Sania Altaf, Taj Muhammad, Farman Ullah, Rida Naz, Shaista Qazi, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Lower respiratory tract infections attack the airways below the larynx, including the trachea and alveolar sacs. It is related to infants and young children more frequently. Purpose: Therefore, this study was conducted on children less than five years to determine their LRTI epidemiological trends. Methods: The study comprised 761 children up to 5 years old who were presented at the outpatient department (OPDs) and were admitted to Tertiary care hospitals in district Dera Ismail Khan, Lakki Marwat and Tank from January 2022 to January 2023. Results: The study included 488 boys (64.12%) and 273 girls (35.87%), diagnosed with LRTIs. Our findings revealed that the LRTI showed the highest incidence in infants (p<0.05) with less than a year of age (327/761). Female children (57.03) in our study were most often infected (p<0.05) with LRTIs than males (42.96%), respectively. Significantly lower-weighed children were more prone to the infection (p<0.05) of weight less than 10 Kg with an incidence of 64.52% and a high proportion (p<0.05) of the infected kids belonged to poor families (85.41%) of mostly (p<0.05) rural area (60.84%). The clinical manifestations were characterized by coughing (93.95%), followed by fever (78.97), phlegm (70.95%), tight chest (42.96%), shortness of breath (36.92%), dyspnea (15.90%) and 14.06% (107/761) children manifested with wheezing sounds during infection. Conclusion: It was concluded that infants had the highest frequency of LRTIs rendering them to hospitalization. Practical Implications: Therefore, public intervention to prevent LRTIs in children should be implemented prior to the seasonal spread of infectious diseases. Keywords: Coughing; Dyspnea; Epidemiology; Phlegm; Wheezing.